Anomalous Surface Compositions of Stoichiometric Mixed Oxide Compounds - Merzlikin, Sergiy V. (2010)
The surface compositions of bulk mixed metal oxides stoichiometric vanadate and molybdate compounds have been systematically examined, for the first time, by combined synchroton-based depth-resolved XPS profile analysis, conventional XPS and LEIS spectroscopy. The outer surfaces of many, but not all, of the bulk mixed vanadates and molybdates tend to be enriched with surface VOx and MoOx species approaching monolayer coverage. Furthermore, this surface enrichment phenomenon can be dramatically enhanced in the presence of minor amount of alkali impurities. These new findings have significant implications for the fundamental understanding of how bulk mixed oxide materials function in numerous technical applications.